2008
DOI: 10.1038/sj.bjc.6604334
|View full text |Cite
|
Sign up to set email alerts
|

Single-step doxorubicin-selected cancer cells overexpress the ABCG2 drug transporter through epigenetic changes

Abstract: Understanding the mechanisms of multidrug resistance (MDR) could improve clinical drug efficacy. Multidrug resistance is associated with ATP binding cassette (ABC) transporters, but the factors that regulate their expression at clinically relevant drug concentrations are poorly understood. We report that a single-step selection with low doses of anti-cancer agents, similar to concentrations reported in vivo, induces MDR that is mediated exclusively by ABCG2. We selected breast, ovarian and colon cancer cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 34 publications
5
85
0
Order By: Relevance
“…16 Similarly, Calcango et al reported that exposure of breast, ovarian and colon cancer cells to low concentrations of doxorubicin for 10 days resulted in development of resistance that was associated with down-regulation of HDAC1. 17 MicroRNAs have been reported previously to induce chemo resistance of cancer cells by different mechanisms such as modulation of intracellular drug concentrations, modulation of drug target, enhancement of drug metabolism, inhibition of apoptosis, regulation of angiogenesis and generation of tumor stem cells. [18][19][20][21][22][23] Among the 14 miRNAs dysregulated in the present study in A549DOX11 cells, 4 (has-miR-1973, 494, 4286 and 29b-3p) have shown the highest level of upregulation (2.99 -4.44 folds) compared with the A549 parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, Calcango et al reported that exposure of breast, ovarian and colon cancer cells to low concentrations of doxorubicin for 10 days resulted in development of resistance that was associated with down-regulation of HDAC1. 17 MicroRNAs have been reported previously to induce chemo resistance of cancer cells by different mechanisms such as modulation of intracellular drug concentrations, modulation of drug target, enhancement of drug metabolism, inhibition of apoptosis, regulation of angiogenesis and generation of tumor stem cells. [18][19][20][21][22][23] Among the 14 miRNAs dysregulated in the present study in A549DOX11 cells, 4 (has-miR-1973, 494, 4286 and 29b-3p) have shown the highest level of upregulation (2.99 -4.44 folds) compared with the A549 parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation occurs predominantly at CpG sites in the mammalian genome by the DNA methyltransferase (DNMT) enzymes. The majority of CpG pairs are chemically modified by the covalent attachment of a methyl group to the C 5 position of the cytosine ring (Tate & Bird, 1993;Calcagno et al, 2008). Methylation of DNA is regarded as a means of regulating gene expression through two general mechanisms.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…Our findings suggest that this chemosensitization could depend on down-regulation of ABCG2, which was strongly down-regulated after SOX2 silencing. Indeed, both chemotherapeutic agents are ABCG2 substrates (30,31), and Zheng and co-workers (32) showed that ABCG2 has a major responsibility for side population (stem cell-like subpopulation) resistance to doxorubicin in ATC treatment. Hence, our data strongly support a hierarchical model in which SOX2 plays a central role.…”
mentioning
confidence: 99%